The impact of mandatory economic education on adolescents' attitudes - Luis Oberrauch; Günther Seeber (ZBW – Leibniz Information Centre for Economics, 2021)
Various studies have examined how the study of economics affects students' views on economic phenomena, yet there is little evidence regarding its impact on teenagers. We study the effect of a recent curriculum reform introducing mandatory economic education on teenagers' attitudes towards economics in Southwest Germany. Our findings reveal that students affected by the reform show, on average, more interest in economics, see money as more important and expect more social responsibility from companies. Conversely, we don't observe differences in attitudes towards competition. Regarding socio-economic characteristics, our data reveal strong gender differences already before adulthood.
Keywords: A21; D14; I20; 330; Pre-college economic education; economic attitudes; economic competence; gender gap